Revision of the New World species of Stiphrosoma Czerny (Diptera: Anthomyzidae). - Roháček, Jindřich; Barber, Kevin N. (Contributions to Entomology = Beiträge zur Entomologie, 2005)
The species of the genus Stiphrosoma Czerny, 1928 found in the New World are revised. Fourteen species are recognized, including the type species of the genus, S. sabulosum (Haliday, 1837), and 13 new species, viz. S. pectinatum sp. n. (Canada: Ontario, Quebec; USA: District of Columbia, Georgia, Illinois, Indiana, Maryland, Massachusetts, Michigan, New York, North Carolina, Pennsylvania, Tennessee, Virginia, West Virginia), S. lucipetum sp. n. (Bahamas; Belize; Costa Rica; Cuba; USA: Florida), S. pullum sp. n. (Costa Rica), S. setipleurum sp. n. (Canada: New Brunswick, Nova Scotia, Ontario, Quebec; USA: Illinois, Indiana, Massachusetts, Michigan, New York, Pennsylvania, West Virginia), S. balteatum sp. n. (Canada: Ontario, Quebec; USA: District of Columbia, Illinois, Massachusetts, Michigan, New York, Ohio, Tennessee, Wisconsin), S. hirtum sp. n. (Canada: Alberta, Manitoba, Ontario, Saskatchewan; USA: Colorado, Minnesota, Montana, North Dakota, Utah), S. artum sp. n. (Canada: Alberta, Saskatchewan; USA: North Dakota), S. helvum sp. n. (Canada: Alberta; USA: Montana), S. stylatum sp. n. (Canada: Manitoba, Ontario; USA: Minnesota, Utah), S. minor sp. n. (USA: Arizona), S. vittatum sp. n. (USA: California), S. sororium sp. n. (Mexico) and S. humerale sp. n. (Canada: Alberta, British Columbia, Manitoba, Newfoundland, Nova Scotia, Ontario, Quebec, Saskatchewan; USA: Michigan, New Hampshire, North Carolina, Tennessee, Vermont, Virginia, Washington; in the Palaearctic - Latvia; North Korea; Russia: Siberia). Descriptions of all species are given along with illustrations of male and female terminalia and other diagnostic structures, and their relationships, biology and distribution are discussed. Occurrence of S. sabulosum in the Nearctic Region is discussed but its presupposed introduction from Europe has not been demonstrated. The Holarctic distribution of S. humerale is regarded as natural; the E. Palaearctic populations of S. humerale were formerly erroneously ascribed to S. laetum (Meigen, 1830). Wing polymorphism is described in two new species, viz. S. hirtum sp. n. and S. artum sp. n., as well as in S. sabulosum. The genus Stiphrosoma is newly diagnosed on the basis of all known species and its relationships are discussed. A key to world species of Stiphrosoma is presented. Keywords Taxonomy, Stiphrosoma, generic diagnosis, 13 new species, key, relationships, biology, distribution, wing polymorphism, New World. Nomenclatural Acts artum Roháček & Barber, 2005 (Stiphrosoma), spec. n. balteatum Roháček & Barber, 2005 (Stiphrosoma), spec. n. helvum Roháček & Barber, 2005 (Stiphrosoma), spec. n. hirtum Roháček & Barber, 2005 (Stiphrosoma), spec. n. humerale Roháček & Barber, 2005 (Stiphrosoma), spec. n. lucipetum Roháček & Barber, 2005 (Stiphrosoma), spec. n. minor Roháček & Barber, 2005 (Stiphrosoma), spec. n. pectinatum Roháček & Barber, 2005 (Stiphrosoma), spec. n. pullum Roháček & Barber, 2005 (Stiphrosoma), spec. n. setipleurum Roháček & Barber, 2005 (Stiphrosoma), spec. n. sororium Roháček & Barber, 2005 (Stiphrosoma), spec. n. stylatum Roháček & Barber, 2005 (Stiphrosoma), spec. n. vittatum Roháček & Barber, 2005 (Stiphrosoma), spec. n.